The stage of online dating relationships in the pandemic era: case study of bumble apps user (Faculty of Communications Science, Dr. Soetomo University, 2021)
In the pandemic era, where physical contact is limited, online dating apps become alternatives for meeting people to form a romantic relationship. One of the newest online dating apps is Bumble, known for its uniqueness where only women can initiate contact. This qualitative research would like to know the stage of online dating relationships using the six stages in DeVito's relationship model, using the constructivist paradigm and case study as a method. The research data is collected through interviews and observation. The study found that the women always initiate the contact stage due to the characteristic of the apps. The involvement would happen in other mediums such as messaging apps. It is hard to reach the stage of intimacy since the pandemic limits their chance to meet in person. And as the intimacy level is hard to achieve, when there is deterioration, the participant chooses to exit the relationship rather than repair it first. Keywords: Online Dating; Bumble; Pandemic; Relationship Stages.